Employee Identification and Wages: On the Economics of "Affective Commitment" - Patrick Kampkötter; Lea Petters; Dirk Sliwka (Institute of Labor Economics (IZA), 2020)
We study the role of employees' identification to the employer for wage growth. We first show in a formal model that identification implies countervailing effects: Employees with higher identification are more valuable as they exert higher efforts, but have weaker bargaining positions, and less outside options as they search less. Analyzing a novel representative panel dataset, we find that stronger identification is associated with less job search and turnover. Workers that have higher identification exhibit significantly lower wage growth. In line with the model, this pattern tends to be reversed conditional on having obtained an external offer.
Keywords: J31; M50; M52; 330; wage; affective commitment; identity; turnover; job search